Detection and genetic analysis of the enteroaggregative Escherichia coli heat-stable enterotoxin (EAST1) gene in clinical isolates of enteropathogenic Escherichia coli (EPEC) strains - Silva, Lucas EP (BioMed Central, 2014)
BACKGROUND: The enteroaggregative E. coli heat-stable enterotoxin 1 (EAST1) encoded by astA gene has been found in enteropathogenic E. coli (EPEC) strains. However, it is not sufficient to simply probe strains with an astA gene probe due to the existence of astA mutants (type 1 and type 2 SHEAST) and EAST1 variants (EAST1 v1-4). In this study, 222 EPEC (70 typical and 152 atypical) isolates were tested for the presence of the astA gene sequence by PCR and sequencing. RESULTS: The astA gene was amplified from 54 strains, 11 typical and 43 atypical. Sequence analysis of the PCR products showed that 25 strains, 7 typical and 18 atypical, had an intact astA gene. A subgroup of 7 atypical strains had a variant type of the astA gene sequence, with four non-synonymous nucleotide substitutions. The remaining 22 strains had mutated astA gene with nucleotide deletions or substitutions in the first 8 codons. The RT-PCR results showed that the astA gene was transcribed only by the strains carrying either the intact or the variant type of the astA gene sequence. Southern blot analysis indicated that astA is located in EAF plasmid in typical strains, and in plasmids of similar size in atypical strains. Strains carrying intact astA genes were more frequently found in diarrheic children than in non-diarrheic children (p < 0.05). CONCLUSION: In conclusion, our data suggest that the presence of an intact astA gene may represent an additional virulence determinant in both EPEC groups.